1980
DOI: 10.1063/1.524396
|View full text |Cite
|
Sign up to set email alerts
|

A concise and accurate solution for Poiseuille flow in a plane channel

Abstract: The recently developed FN method of solving problems in particle transport theory is used to establish a concise and accurate solution for the flow of a rarefied gas between two parallel plates. The Bhatnagar, Gross, and Krook model is used, and numerical results are given for a wide range of the Knudsen number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…[9] and [10] for the various problems we have solved here, and we have confirmed precisely the Poiseuille-flow results from Ref. [23]. In addition, we have increased the value of N used in our computations until we found stability in the final results.…”
Section: Numerical Resultssupporting
confidence: 66%
“…[9] and [10] for the various problems we have solved here, and we have confirmed precisely the Poiseuille-flow results from Ref. [23]. In addition, we have increased the value of N used in our computations until we found stability in the final results.…”
Section: Numerical Resultssupporting
confidence: 66%
“…An alternative form for the flow rate can be obtained by following the projection procedure outlined in [5] in terms of the outgoing surface perturbation:…”
Section: Formulation Of the Dvm Equationsmentioning
confidence: 99%
“…A second set of benchmarks can be found in [5]. These results are for no accommodation at the surfaces (α = 1) and a wide variety of channel widths.…”
Section: The Flow Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The reader is referred to [1][2][3][4][5][6], and other references therein for an overview of the recent work in this area. Earlier researches [7][8][9][10][11][12] solved rarefied gas dynamics problems using different methods. It has been shown that these methods yield good results.…”
Section: Introductionmentioning
confidence: 99%